Elastomeric Respirators for COVID-19 and the Next Respiratory Virus Pandemic: Essential Design Elements. (19th October 2021) - Bowdle, T. Andrew; Jelacic, Srdjan; Munoz-Price, L. Silvia; Cohen, Marty; M., Sai Krishna; Brosseau, Lisa
Abstract : Respiratory viruses are transmitted via respiratory particles that are emitted when people breath, speak, cough, or sneeze. These particles span the size spectrum from visible droplets to airborne particles of hundreds of nanometers. Barrier face coverings ("cloth masks") and surgical masks are loose-fitting and provide limited protection from airborne particles since air passes around the edges of the mask as well as through the filtering material. Respirators, which fit tightly to the face, provide more effective respiratory protection. Although healthcare workers have relied primarily on disposable filtering facepiece respirators (such as N95) during the COVID-19 pandemic, reusable elastomeric respirators have significant potential advantages for the COVID-19 and future respiratory virus pandemics. However, currently available elastomeric respirators were not designed primarily for healthcare or pandemic use and require further development to improve their suitability for this application. The authors believe that the development, implementation, and stockpiling of improved elastomeric respirators should be an international public health priority. Abstract : Respirators provide reliable protection from airborne respiratory pathogens. Reusable elastomeric respirators offer potential advantages compared to disposable filtering facepiece respirators. Development of improved elastomeric respirators should be an international public health priority.